The Cricotopus (Oliveiriella) (Diptera: Chironomidae) of the High Altitude Andean Streams, with Description of a New Species, C. (O.) rieradevallae - Prat, N. (2017)
The genus Oliveiriella (Chironomidae, Orthocladiinae) was erected by Wiedenbrug & Fittkau (1997). The adults have characteristic black spots on their wings and other characteristics similar to the genus Cricotopus. Pupal skins are very characteristic with strong short spines in the anal lobe instead of setae, while larvae are distinguishable by the long anal papillae and the intense blue color of their body. However, Andersen et al (2013) consider Oliveiriella as a subgenera of Cricotopus. In this paper, using the sequences of the cox1 gene, we conclude that Oliveiriella should be considered a subgenus within Cricotopus, confirming its status in Andersen et al (2013). Furthermore, we describe Cricotopus (Oliveiriella) rieradevallae Prat & Paggi sp. n. from the Saltana river (Ecuador). The adult males, females, and preimaginal stages of the two species of subgenus Oliveiriella known from South America Cricotopus (O.) almeidai n. comb. from Peru, Brazil, and Argentina and Cricotopus (O.) sanjavieri n. comb. from Argentina are compared with those of Cricotopus (O.) rieradevallae sp. n. from Ecuador. The differences allow the distinction of the three species. The cox1 gene reveals that at least three different undescribed species of the same subgenus are present in the high-altitude tropical Andes. The morphology of the available pupae and pupal exuviae reveals the presence of several morphotypes that are candidates to be described as new species. A key used to distinguish these pupal morphotypes is provided, including the three described species. Additionally, the distribution of the subgenus is discussed.